1996
DOI: 10.1007/bf00311552
|View full text |Cite
|
Sign up to set email alerts
|

Ventral pancreatic resection for adenoma and low-grade malignancies of the head of the pancreas

Abstract: The head of the pancreas can be anatomically divided into two sections, one drained by the duct of the Santorini system, and the other drained by the ventral pancreatic duct. This study was undertaken to determine whether independent resection of the ventral pancreas drained by the ventral pancreatic duct could be performed safely and effectively, by employing the following method in four patients. First, the duodenum and pancreas were sufficiently separated preserving the mesoduodenum and the posterior pancre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The extent of the embryologically ventral primordium of the head of the pancreas has been considered to correspond to the caudal part of the head of the pancreas, including the uncinate process, but this was not based on any clear anatomical evidence. [4][5][6][12][13][14][21][22][23] However, recent immunohistochemical studies with PP cells, 18,19,24 anatomical dissections using fetuses 15 or adults, 25,26 and the current study suggest that the embryonic fusion occurs along a rather horizontal plane, that is to say, the anterior component of the inferior head of the pancreas including the uncinate process belongs to the dorsal primordium, although some anomalies may be encountered. 25 The ventral pancreas has a close relationship with the common bile duct.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The extent of the embryologically ventral primordium of the head of the pancreas has been considered to correspond to the caudal part of the head of the pancreas, including the uncinate process, but this was not based on any clear anatomical evidence. [4][5][6][12][13][14][21][22][23] However, recent immunohistochemical studies with PP cells, 18,19,24 anatomical dissections using fetuses 15 or adults, 25,26 and the current study suggest that the embryonic fusion occurs along a rather horizontal plane, that is to say, the anterior component of the inferior head of the pancreas including the uncinate process belongs to the dorsal primordium, although some anomalies may be encountered. 25 The ventral pancreas has a close relationship with the common bile duct.…”
Section: Discussionmentioning
confidence: 65%
“…However, reports of ventral pancreatectomy 4,5 have provided no anatomical evidence that the resected parenchyma belonged to the embryologically ventral primordium; rather, it appears to be a resection of the inferior head of the pancreas. The current study analyzed the anatomical structure of the head of the pancreas by surgical dissection of autopsy specimens to provide a concrete guide for segmental resection of the head of the pancreas along the embryological fusion plane (ie, resection of the dorsal or ventral primordium).…”
Section: Surgerymentioning
confidence: 92%
“…Until now, various types of organ-preserving pancreatectomy have been introduced such as duodenum-preserving pancreatic head resection (DPPHR), pancreatic head resection with segmental duodenectomy (PHRSD), central pancreatectomy (CP), ventral pancreatectomy (1), segmental resection of pancreas (2), ductal branch-oriented minimal pancreatectomy (3), and spleen-preserving distal pancreatectomy (SPDP). It has been suggested that a limited resection has the advantage of preserving function of the pancreas and the organs around pancreas (4-8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new concept of pancreatic segmentation based on embryology has been suggested, and limited pancreatectomy for benign tumors and low-grade malignancies has been reported (14-16). Ryu et al (14) performed a ventral pancreatic resection for adenoma and low-grade malignancy of the uncinate process of the pancreas. The resection is systemic because it takes the ventral pancreas away including Wirsung's duct along the anatomic ductal structure of the pancreas.…”
Section: Drainage Area Of the Inferior Branchmentioning
confidence: 99%